Necesidad de reformar el código tributario por lacerar el derecho al trabajo, consagrado en la constitución de la república del Ecuador. - Iñiguez Luna, Mario Adrián (2018)
The Constitution of the Republic of Ecuador establishes textually the guarantees and the right to work of citizens, in every sense of the word work, whether traders, public or private employees. It concretándome the development of my research focuses solely to the worker particular character, that is the trader who bet their investment in product sales of social consumer, more specifically the retailer, wholesaler or retailer who conducts business in all the cities of Ecuador. As for the theoretical framework I will address concepts and principal parameters, because it is a very important medium in which the salient terms of the problem, this in order to have a clearer, accurate and concise understanding of respect is analyzed work and taxes, in the development of this research work. the legal and commercial importance of the right of conceptualization work will also be discussed, as is the activity that try to excel many Ecuadorian families reference to the historical background of the tribute will be made in all its forms in the doctrinal framework, starting with the universal rise of income tax, until the rise in our country as an almost inescapable obligation in our society. serious problems as a result of closed shop, and the impact that brings the lack of comprehensive and economic development of people was also highlighted. In this framework a thorough study of the implications involved the closure of small businesses will be adopted. the legal nature and the fundamental characteristics of these measures usually taken by the executive branch will also analyze, and others by the Assembly as appropriate attributions them; and finally reference will be made to study and importance of labor law established in our Ecuadorian Constitution. In the legal framework will be discussed, the Constitution of the Republic of Ecuador, Tax Code, the Law Reform Public Finance, using primarily the analysis corresponding to the closure of commercial retail and wholesale; and finally the study of the laws of Mexico, Peru and Chile, to determine the application of other external measures in later compared with our legislation and reach a favorable legal analysis that can benefit the improvement of laws and a better quality of life for our society. In the analysis and verification of results, it has addressed the study of this project to field research, mainly with regard to the opinions and judgments of professionals is directly linked to the development of this research. And finally I will do Conclusions and Recommendations on the fundamental aspects of the issue raised, which the possible solution of the problem is addressed by the conclusive analysis; like wise it is proposed to the National Constituent Assembly reform that benefits the merchant rights as an independent worker.